ORGANIZING GROUP WORK IN CLASSROOM INSTRUCTION - Qahramon Fozilov (Web of Journals Publishing, 2025)
This paper discusses the organization of small group work in the classroom, including the components of group work during the lesson, planning for group division, adapting the classroom layout accordingly, the preparation stage, and the structure of group work.
Keywords: Lifelong learning, modern pedagogical technologies, form, method, tool, approach, student grouping, small group work.